The Role of Social Media in the Religiosity of Islamic Adolescents Through a Descriptive Qualitative Approach - Agnes Widiana; Iu Rusliana; Busro Busro (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research aims to analyze and determine the role of social media in influencing religious doctrinal, ritual experiences, and socio-religious interactions among students at SMA Negeri 1 Cibitung. Qualitative with a phenomenological approach is the type researchers apply and use for this research, the data sources used are primary and secondary data. The data techniques collection used are depth interviews, and FGD (Focus Group Discussion). The research results show that social media helps students think about religion, increase their level of religiosity, obey religious commandments, and remember God more often. In addition, online communities on social media play an important role in supporting religiosity through interaction, discussion, and moral and emotional support. Although there is a small percentage of students who feel confused about certain religious concepts, the majority feel helped by the content they consume on social media. This research provides new contributions in understanding how social media can be used as an effective tool to support religious education and practice among the zillennial generation.